2017
DOI: 10.1038/s41598-017-09648-6
|View full text |Cite
|
Sign up to set email alerts
|

Neglected role of hydrogen sulfide in sulfur mustard poisoning: Keap1 S-sulfhydration and subsequent Nrf2 pathway activation

Abstract: Sulfur mustard (SM) is a chemical warfare agent and a terrorism choice that targets various organs and tissues, especially lung tissues. Its toxic effects are tightly associated with oxidative stress. The signaling molecule hydrogen sulfide (H2S) protects the lungs against oxidative stress and activates the NF-E2 p45-related factor 2 (Nrf2) pathway. Here, we sought to establish whether endogenous H2S plays a role in SM induced lesion in mouse lungs and lung cells and whether endogenous H2S plays the role throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 59 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…In contrast, PAG administration further exacerbated lung injuries. Moreover, Meng et al (2017) also documented that PAG has exacerbated lung damage through reduction of endogenous H 2 S level, CSE expression and Nrf2 nuclear translocation which was associated with increased oxidative stress markers. Zhao et al (2014) reported that H 2 S donors have been widely used in the field.…”
Section: Immunohistochemical Assessment Of Inosmentioning
confidence: 90%
“…In contrast, PAG administration further exacerbated lung injuries. Moreover, Meng et al (2017) also documented that PAG has exacerbated lung damage through reduction of endogenous H 2 S level, CSE expression and Nrf2 nuclear translocation which was associated with increased oxidative stress markers. Zhao et al (2014) reported that H 2 S donors have been widely used in the field.…”
Section: Immunohistochemical Assessment Of Inosmentioning
confidence: 90%
“…The present experiments show that simple but specific hydroxybenzenes can oxidize H 2 S to polysulfides after the former are themselves autoxidized. These results help to explain the mechanism behind the health benefits of many nutraceutical polyphenols; polysulfides produced by the oxidation of H 2 S are potent antioxidants [ 17 ], they may scavenge superoxide [ 42 ], and through their ability to persulfidate Keap1, they free it from Nrf2, which can then activate nuclear antioxidant response elements [ 18 , 19 , 43 , 44 , 45 , 46 ]. Our experiments also show that the ability of hydroxybenzenes to oxidize H 2 S varies considerably with the location and distribution of these hydroxyl groups and that the addition of specific side groups can further alter the reactivity of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term benefits of polysulfides are also derived from their modulation of antioxidant response mechanisms. Polysulfides increase intracellular antioxidant activity via persulfidation of Keap1 which causes Keap1 to dissociate from Nrf2, similar to the proposed mechanism of Keap-1 peroxidation [34][35][36][37][38][39]. Nrf2 then translocates to the nucleus where it activates the suite of cytoprotective antioxidant response elements [40,41].…”
Section: Antioxidant Function Of Mnp-generated Polysulfidesmentioning
confidence: 85%